2009
DOI: 10.1007/s12576-008-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of aquaporin-5 in differentiation of human gastric cancer cells

Abstract: Litttle is known about the function of aquaporin (AQP) water channels in human gastric cancer. In the upper or middle part of human stomach, we found that expression level of AQP5 protein in intestinal type of adenocarcinoma was significantly higher than that in accompanying normal mucosa. AQP5 was localized in the apical membrane of the cancer cells. On the other hand, both AQP3 and AQP4 were not up-regulated in the adenocarcinoma. To elucidate the role of AQP5 in cancer cells, AQP5 was exogenously expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Watanabe et al reported that exogenous expression of AQP5 significantly increased the differentiated proportion of a human gastric adenocarcinoma cell line [40]. Kong et al described that AQP4 deletion in ANSCs preferentially impaired the neuronal differentiation rather than glial differentiation.…”
Section: Aqp5 Deletion Increases Differentiation Capacity Of Mscsmentioning
confidence: 99%
“…Watanabe et al reported that exogenous expression of AQP5 significantly increased the differentiated proportion of a human gastric adenocarcinoma cell line [40]. Kong et al described that AQP4 deletion in ANSCs preferentially impaired the neuronal differentiation rather than glial differentiation.…”
Section: Aqp5 Deletion Increases Differentiation Capacity Of Mscsmentioning
confidence: 99%
“…Overexpression of several AQPs has been observed in different types of human carcinoma [6,7,8,9,10,11,12,13,14]. We previously reported that AQP-5 may be involved in the differentiation of human gastric carcinoma cells [6]. We also analyzed AQP-1, -4, -5, and -8 expression immunohistochemically using tissue microarray (TMA) in 81 biliary tract carcinoma samples [15].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that AQP-5 may be involved in differentiation of human gastric carcinoma cells, and overexpression of several aquaporins has been reported in different types of human carcinoma (8)(9)(10)(11)(12)(13)(14)(15)(16). However, the role of AQPs in biliary tract carcinogenesis has not yet been clearly defined.…”
Section: Introductionmentioning
confidence: 99%